Mesophotic coral depth acclimatization is a function of host-specific symbiont physiology - Ziegler, Maren; Roder, Cornelia M.; Büchel, Claudia; Voolstra, Christian R. (Frontiers in Marine Science, 2015)
Mesophotic coral ecosystems receive increasing attention owing to their potential as deep coral refuges in times of global environmental change. Here, the mechanisms of coral holobiont photoacclimatization over a 60 m depth gradient in the central Red Sea were examined for the four coral genera Porites, Leptoseris, Pachyseris, and Podabacia. General acclimatization strategies were common to all host-symbiont combinations, e.g. Symbiodinium cell densities and photoprotective to light-harvesting pigment ratios both significantly decreased with water depth. Porites harboured Symbiodinium type C15 over the whole 60 m depth range, while Pachyseris and Podabacia had limited vertical distributions and hosted mainly Symbiodinium type C1. Symbiodinium type C15 had generally higher xanthophyll de-epoxidation rates and lower maximum quantum yields than C1, and also exhibited a strong photoacclimatory signal over depth that relates to the large distribution range of Porites. Interestingly, the coral host had an effect on Symbiodinium pigment composition. When comparing Symbiodinium type C1 in Podabacia and Pachyseris, the ß-carotene chl a-1, the peridinin chl a-1, and diadinoxanthin chl a-1 ratios were significantly different between host species. Our data support a view that depth acclimatization of corals in the mesophotics is supported by Symbiodinium physiology, which in turn is host-specific.